Spatial Varying Relationship between Financial Development and New Firm Formation: Evidence from a Developing Country - Can Karahasan, Burhan (Panoeconomicus, 2018)
This study investigates the spatial varying relationship between financial development and new firm formation in Turkey. Even preliminary findings show that regional financial development spurs new firm formation; evidence from Geographically Weighted Regression stresses the heterogeneous impact of finance, which mostly favours the developed regions. Results for the 2002 to 2009 epoch show impact of finance fluctuates within a range of 0.189 for deposits and 0.082 for credits with the lowest impact observed in Eastern Turkey. This points to the necessity of considering the spatial heterogeneity of regional policies, which underlines that one size does not fit all regions.Key words: Finance, GWR, New firms, Regional development.JEL: R11, R12, R52.Prostorno promenljiv odnos između finansijskog razvoja i nastanak novog preduzeća: podaci iz zemlje u razvojuRad istražuje prostorno promenljive odnose između finansijskog razvoja i nastanka novih preduzeća u Turskoj. Čak i preliminarni nalazi pokazuju da regionalni finansijski razvoj podstiče stvaranje novog preduzeća; dokazi iz geografski ponderisane regresije naglašavaju heterogeni efekat finansiranja, koji uglavnom favorizuje razvijene regije. Rezultati za period od 2002. do 2009. godine pokazuju uticaj finansijskih fluktuacija u rasponu od 0.189 za depozite i 0.082 za kredite sa najnižim uticajem u istočnoj Turskoj. Ovo ukazuje na neophodnost razmatranja prostorne heterogenosti regionalnih politika, što potvrđuje da jedna veličina ne odgovara svim regionima.Ključne reči: Finansije, GWR, nova preduzeća, regionalni razvoj.